1998
DOI: 10.4049/jimmunol.160.4.1555
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Presentation by Dendritic Cells Focuses T Cell Responses Against Immunodominant Peptides: Studies in the Hen Egg-White Lysozyme (HEL) Model1

Abstract: T lymphocyte responses to a protein Ag are restricted to a limited number of determinants and not to all peptides capable of binding to MHC class II molecules. This focusing of the immune response is defined as immunodominance and has been observed with numerous protein Ags. In the H-2d haplotype, hen egg-white lysozyme (HEL)-specific T lymphocytes react with I-Ed-restricted peptides derived from a single immunodominant (ID) region (HEL 103–117). Moreover, we have recently found that another region of HEL (HEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…( 34, 35 ) Kanellopoulos et al reported that DCs focused HEL-specific CD4 + T-cell responses against an I-E d -restricted peptide HEL103-117, while B cells presented an additional I-A d -restricted peptide HEL7-31. ( 36 ) Max Schnurr and colleagues had shown that CD1c + blood DCs and MoDCs were capable of presenting peptides of antigen NY-ESO-1 on both MHC I and MHC II, while pDCs were limited to MHC II presentation. ( 37 ) In this study, antigen UreB adjuvanted different adjuvants induced antigen-specific CD4 + T cell responses in vivo post-vaccination, whereas no peptides of UreB presented by A20 cells were detected in vitro using LC-MS/ MS. One reason may be differences in the cell types of APCs involved, with many APCs subtypes involved in vivo , especially DCs, but only the B cell line (A20) used in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…( 34, 35 ) Kanellopoulos et al reported that DCs focused HEL-specific CD4 + T-cell responses against an I-E d -restricted peptide HEL103-117, while B cells presented an additional I-A d -restricted peptide HEL7-31. ( 36 ) Max Schnurr and colleagues had shown that CD1c + blood DCs and MoDCs were capable of presenting peptides of antigen NY-ESO-1 on both MHC I and MHC II, while pDCs were limited to MHC II presentation. ( 37 ) In this study, antigen UreB adjuvanted different adjuvants induced antigen-specific CD4 + T cell responses in vivo post-vaccination, whereas no peptides of UreB presented by A20 cells were detected in vitro using LC-MS/ MS. One reason may be differences in the cell types of APCs involved, with many APCs subtypes involved in vivo , especially DCs, but only the B cell line (A20) used in vitro .…”
Section: Discussionmentioning
confidence: 99%